Comparison of different CSP technologies for combined power and cooling production. (June 2018) - Ravelli, S.; Franchini, G.; Perdichizzi, A.
Abstract: The present paper deals with the performance prediction of Concentrated Solar Power plants integrated with cooling energy production. The plant configuration is based on a typical steam Rankine cycle (rated 62.1 MWe ). The thermal input is provided by two different solar fields: i) Parabolic Trough Collectors and ii) Central Receiver System with heliostats reflecting on the tower top. In the former case, both north-south and east-west oriented collectors are investigated and compared in the study. A Thermal Energy Storage system allows driving the power block 24-h per day also in periods with low solar irradiation. A steam flow rate extracted from the turbine low stages feeds a set of two-stage absorption chillers, and the produced chilled water is supplied to a district cooling network. A computer code integrating the commercial software Thermoflex and Trnsys has been developed to model and to simulate over 1-year period the solar field and the power block. The power plant is supposed to operate in island mode, having to meet power and cooling demand for a population of about 50, 000 inhabitants in the Saudi desert region. Solar fields and storage system were sized according to a techno-economic optimization algorithm for the minimization of the investment costs. The simulation results show the beneficial effect of the combined power and cooling production in terms of peak load shaving. Compared to the troughs, solar tower exhibits a higher efficiency, thus requiring a lower aperture area and lower investment costs. The techno-economic analysis shows that the axis orientation has a strong impact on the trough collectors and that east-west oriented devices perform better for the investigated load-following application. Highlights: A solar driven Rankine cycle, with cooling production, was simulated in island mode. Parabolic troughs and heliostat field with central receiver were assessed. North-south aligned parabolic troughs required the largest aperture area. Heliostats, with the lowest aperture area, provided the lowest thermal energy surplus. Heliostats with central receiver are the best solution in load-following operation.